2014
DOI: 10.1089/ten.tea.2013.0584
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics of Human-Urine-Derived Stem Cells: Potential for Cell-Based Therapy in Neurology

Abstract: Stem cells in human urine have gained attention in recent years; however, urine-derived stem cells (USCs) are far from being well elucidated. In this study, we compared the biological characteristics of USCs with adipose-derived stem cells (ASCs) and investigated whether USCs could serve as a potential cell source for neural tissue engineering. USCs were isolated from voided urine with a modified culture medium. Through a series of experiments, we examined the growth rate, surface antigens, and differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 36 publications
3
104
0
1
Order By: Relevance
“…We recently confirmed that a subpopulation of cells extracted from voided human urine known as urine-derived stem cells (USCs) have an MSC-like morphology, express MSC surface markers, and maintain a trilineage differentiation capacity in vitro [12,13]. In addition, another team of researchers reported that USCs have the capability to differentiate into endothelial, urothelial and smooth muscle cells [14,15].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…We recently confirmed that a subpopulation of cells extracted from voided human urine known as urine-derived stem cells (USCs) have an MSC-like morphology, express MSC surface markers, and maintain a trilineage differentiation capacity in vitro [12,13]. In addition, another team of researchers reported that USCs have the capability to differentiate into endothelial, urothelial and smooth muscle cells [14,15].…”
Section: Introductionmentioning
confidence: 81%
“…In previous urological studies, USCs were used to construct tissue-engineered conduits for urinary diversion [15] and to ameliorate erectile dysfunction [16,17]. Moreover, we found that USCs combined with bioactive materials accelerated skin-wound healing in rabbits [18] and that USCs can survive in and migrate to other parenchymal areas and differentiate into neuron-like cells in the rat brain [13].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In previous studies, stem-like cells have been extracted from adult urine, which exhibits self-renewal abilities. These cells also showed stem cell markers similar to MSCs with multi-lineage differentiation ability (Fu et al, 2014;Guan et al, 2014;Zhang et al, 2008) and superior proliferation ability. After a serial propagation, hUSCs retained normal karyotypes .…”
Section: Introductionmentioning
confidence: 90%
“…The isolation procedure was performed as described in the literature (Zhang et al 2008;Bharadwaj et al 2011;Guan et al 2014). The cells were cultivated in keratinocyte serum-free medium (KSFM; Invitrogen,USA) and embryonic fibroblast medium in a 1:1 ratio, 10 % heat-inactivated fetal bovine serum, 1 % Pen-Strep antibiotics, and supplemented with 5 ng/ml EGF and 50 ng/ml bovine pituitary extract.…”
Section: Synthesis Of Cap Particles By Fspmentioning
confidence: 99%